2019
DOI: 10.3390/molecules24152705
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of F. esculentum Bee Pollen and Quantitative Analysis of Samples Collected from Seven Areas by HPLC

Abstract: Bee pollen contains all the essential amino acids needed by humans. China is the largest producer of bee pollen in the world. In the present study, we identified 11 fatty acids in F. esculentum bee pollen oil by GC-MS analysis, and 16 compounds were isolated from F. esculentum bee pollen by column chromatography and identified. A high-performance liquid chromatography-diode array detector (HPLC-DAD) method was established for the quality control of F. esculentum bee pollen. A validated HPLC-DAD method was succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Tyrosinase is an enzyme involved in the biosynthesis of melanin in humans, and its inhibitors are of interest for preventing excessive melanin production, as being active ingredients of skin whitening agents. Tyrosinase inhibitory activity (IC 50 : 202.37 μg/mL) of EP was also detected by Bai et al [ 160 ].…”
Section: Endoperoxidesmentioning
confidence: 62%
“…Tyrosinase is an enzyme involved in the biosynthesis of melanin in humans, and its inhibitors are of interest for preventing excessive melanin production, as being active ingredients of skin whitening agents. Tyrosinase inhibitory activity (IC 50 : 202.37 μg/mL) of EP was also detected by Bai et al [ 160 ].…”
Section: Endoperoxidesmentioning
confidence: 62%
“…Bee pollen of safflower is a mixture of the pollen and nectar of safflower and bee gland secretions, which not only supplies nutrition to bees and larvae but is also popular as a nutritional product (Kocot et al, 2018). Polysaccharides are the most abundant components of bee pollen, accounting for 18.9-57.6% of the dried powder (Li et al, 2019). In recent years, an increasing number of studies have shown that PBPC possess a variety of biological effects, such as antioxidant, immunomodulatory, antitumor, anticoagulant and antibacterial activities (Li et al, 2017c;Zuo et al, 2017;Wang et al, 2019b;Chen et al, 2019;Wang et al, 2019c;Shi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Like other bee products, the bioactivities of bee pollen depended mainly on the plant origin and its geographical region (Arruda et al, 2013). In addition, the reported activity following fractionation is influenced by the extraction methods, extraction solvents, extraction numbers and extraction times (Li et al, 2019), as well as the assay conditions.…”
Section: Introductionmentioning
confidence: 99%